The Transition to the Metallic State in Polycrystalline n‐type Doped ZnO Thin Films1. Issue 6 (3rd April 2014) - Vai, Alex T.; Kuznetsov, Vladimir L.; Jain, Himanshu; Slocombe, Daniel; Rashidi, Nazanin; Pepper, Michael; Edwards, Peter P.
Abstract We report a detailed investigation of the charge carrier transport in polycrystalline n‐type impurity‐doped zinc oxide (ZnO) thin films grown by spray pyrolysis over a wide range of carrier concentrations. Particular attention is devoted to a study of the composition‐dependent metal‐insulator transition (MIT) in this transparent conducting oxide (TCO). In order to describe the flow of electrons in these impurity‐doped thin films over this full range of conditions, it is necessary to consider multiple electronic conduction processes. The first conduction process arises from current carriers thermally excited from impurity states into the (host) ZnO conduction band. The second involves thermally‐activated, quantum‐mechanical tunnelling within an impurity band located close to the host conduction band. The latter conduction process predominates at low temperatures whilst the former dominates at high temperatures. We find that a MIT occurs at a critical carrier concentration between 2 and 6 × 1019 cm–3. At higher concentrations in this metallic regime, the impurity band merges with the ZnO conduction band. The location of the MIT was determined from low temperature resistivity data and the results are discussed in terms of the Mott and Ioffe‐Regel models. In addition, the overriding importance of grain boundaries is highlighted for these polycrystalline thin films; this is a key factor in determining and limiting electronic conduction in these samples, particularly at high temperatures. These results highlight the practical importance of understanding both the MIT and also grain boundary effects in determining the electrical performance of polycrystalline TCO films.